Processing GPS/GLONASS data - Hai, Vy Quoc (Vietnam Journal of Earth Sciences, 2014)
The GPS/GLONASS data processing and application of two (or more) global positioning system offers manypractical benefits. In this paper, some GNSS data of IGS sites (BAKO, COCO, NTUS and LHAZ) has been collectedand processed by Bernese 5.0 software.The results show that, baseline processing achieved satisfactory accuracy with relative error about 1/764 000 000,error of adjusted coordinates smaller than 2 mm in large spatial scales network- the distance about 4500km.Based on of those parameters, a conclusion can be made, GPS/GLONASS data absolutely fulfill requirements ofinvestigation crustal movements.ReferencesAlexei E. Zinoviev, Topcon PositioningSystems CIS, LLC, 2005. Using GLONASS in20combined GNSS Receivers: Current Status. IONGNSS 18th International Technical Meeting of theSatellite Division, 13-16 September 2005, LongBeach, CA.Bykhanov, E., 1999. Timing and Positioningwith GLONASS and GPS”. GPSSolution, Vol. 3,No.1, pp. 26-31.C. Boucher, Z. Altamimi, 2001. ITRS, PZ-90 and WGS-84: curent realization and the relatedtransformation parameters. Journal of Geodesy, 75,613-619.M. P. Stewart1 et al., 2000. Thecontribution of GLONASS measurements toregional and continental scale geodetic monitoringregimes. Earth Planets Space, 52, 877-880.Mitrikas, V. V., S.G. Revnivykh, E.V.Bykhanov, 1998. WGS84/PZ90 transformationparameters determination based on laser andephemeris long-term GLONASS orbital dataprocessing. Proceedings of ION-GPS 98, theInstitute of Navigation, Part II, pp. 1625-1635.Rolf Dach, Urs Hugentober, Peter Walser, 2008. Bernese GPS Software Version 5.0.Astronomical Institute, University of Bern.Vy Quốc Hải, 2010. Xử lý số liệu GLONASS phục vụ nghiên cứu địa động lực. Tạp chí Các Khoa học về Trái Đất, T.30, 4, tr.343-347.Vy Quốc Hải, 2013. So sánh kết quả xử lý số liệu GPS và GLONASS. Tạp chí Các Khoa học về Trái Đất, T.35, 1, tr.60-65.